A study of the pattern guide and the Dankmeijer skin striae guide in patients with schizophrenia (Journal of the College of Basic Education, 2022)
The skin lines of 240 patients with chronic schizophrenia were compared with those of healthy individuals in both the phenotypic density index and the Dunckmager index. The results showed an increase in the pattern density index in schizophrenia patients compared to the standard samples, due to the increase in the numbers of rounders that have more than one delta compared to the standard samples.As for the Dankmijer index, it was observed that the values ​​of this indicator were lower in the sample of female patients (12.98) compared to the standard female sample (15.48), while the values ​​of this indicator were higher in male patients with schizophrenia (9.39) compared to the standard sample (5.45).